Perayaan Mitos Dalam Film Horor Indonesia Analisa Struktural dan Implikasi Sosial Keagamaan - Achmad Nur (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2016)
This paper examines the horror genre in Indonesia film with three movie titles consisting of "Si Manis Jembatan Ancol, Beranak dalam Kubur, Malam Satu Suro." The academic interest that started this article is created by the myth in the Java community about the rise of spirits roaming, terrorizing, and even threatening the safety of the public. Questions that will be answered in this paper is how the images of myths are displayed and the culture represented in the narrative film. Structuralism will be used to answer this question. Claud Levi-Strauss insists on tracking structures on film and cultural studies and Stuart Hall with the concept of representation emphasizes the search for meaning behind the structure. After analysis, it appears in the narrative of the film a consolidation myth about ghosts as a representation of Javanese culture, which believed in animism and dynamism. The three titles in this paper, indicate that bad deeds will have an negative impact. Historically the religious phenomenon is contrary to the Islamic religion, but is sociologically meaningful self evaluation in determining attitudes and behavior at the beginning of the entry of Islam in Java.